PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, MUTASI KERJA TERHADAP KINERJA PEGAWAI SEKRETARIAT DAERAH KOTA PEKANBARU MELALUI KOMITMEN KERJA - Arasyid Putera; Marnis; Yusni Maulida (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2019)
Research focus on lack performance of Employee in Major’s Office has an impact to the people that has to be served in Major’s Service even tough the employee has been placed with merit system and the tangible asset of Major Office has been renovated to give the employee comfort situtaion. This study used the Partial Least Square approach with a population of Emplyee of Pekanbaru Major Officeof 148 employee, and became saturated samples in the study, which gave responses to question items in the research instrument in the form of research questionnaires. The results revealed that a effective leadership exsist by a caring manner to the employee and so do the relative. This research finding show that office layout need to be adaptive to the distribution of information to make the employee can work effectively and has more commitment to their work.